2018
DOI: 10.1155/2018/7148515
|View full text |Cite
|
Sign up to set email alerts
|

Critical Contextual Elements in Facilitating and Achieving Success with a Person-Centred Care Intervention to Support Antipsychotic Deprescribing for Older People in Long-Term Care

Abstract: Antipsychotic and other tranquilising medicines are prescribed to help care staff manages behaviour in one-quarter of older people living in Australian long-term care homes. While these medicines pose significant health risks, particularly for people with dementia, reliance on their use occurs when staff are not educated to respond to resident behaviour using nonpharmacological approaches. The Halting Antipsychotic use in Long-Term care (HALT) single-arm study was undertaken to address this issue with 139 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 29 publications
2
42
0
11
Order By: Relevance
“…The finding that nursing staff were the most common drivers of represcribing, or abandoned deprescribing, is consistent with several studies demonstrating that physicians feel pressure to prescribe sedating medications when requested by long‐term aged care staff . Nursing staff, especially those who are inexperienced or time‐poor, may find it difficult to implement nonpharmacological approaches to manage BPSD and are subsequently vulnerable to overreliance on psychotropic medications . Organisational factors such as inadequate staffing, managerial expectations, and teamwork between staff and visiting health professionals can contribute to a “prescribing culture” within a facility .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The finding that nursing staff were the most common drivers of represcribing, or abandoned deprescribing, is consistent with several studies demonstrating that physicians feel pressure to prescribe sedating medications when requested by long‐term aged care staff . Nursing staff, especially those who are inexperienced or time‐poor, may find it difficult to implement nonpharmacological approaches to manage BPSD and are subsequently vulnerable to overreliance on psychotropic medications . Organisational factors such as inadequate staffing, managerial expectations, and teamwork between staff and visiting health professionals can contribute to a “prescribing culture” within a facility .…”
Section: Discussionsupporting
confidence: 79%
“…While nursing staff reported that nonpharmacological approaches were insufficiently effective in managing BPSD, HALT nurse champions often felt that the antipsychotic was not needed despite another nurse driving its represcription. As previously reported, nurse champions reported reluctance to deprescribe among their colleagues as a key challenge in the implementation of HALT. Our “train‐the‐trainer” model of implementation may have sometimes been insufficient, and more ongoing support and reinforcement may be required.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations